Managerialism and nursing : beyond oppression and profession - Traynor, Michael, 1956- (Routledge, 1999)
Managerialism and Nursing examines the effect of new management strategies on nurses, their morale and the profession as a whole. Using an innovative study of nurses conducted by the Royal College of Nursing, Michael Traynor analyses the relationship between nurses and their managers, looking at the contrasting ways in which each group argues its case and presents its identity.